Organization of Circadian Behavior Relies on Glycinergic Transmission - Frenkel, Lia (2017)
The small ventral lateral neurons (sLNvs) constitute a central circadian pacemaker in the Drosophila brain. They organize daily locomotor activity, partly through the release of the neuropeptide pigment-dispersing factor (PDF), coordinating the action of the remaining clusters required for network synchronization. Despite extensive efforts, the basic principles underlying communication among circadian clusters remain obscure. We identified classical neurotransmitters released by sLNvs through disruption of specific transporters. Adult-specific RNAi-mediated downregulation of the glycine transporter or impairment of glycine synthesis in LNv neurons increased period length by nearly an hour without affecting rhythmicity of locomotor activity. Electrophysiological recordings showed that glycine reduces spiking frequency in circadian neurons. Interestingly, downregulation of glycine receptor subunits in specific sLNv targets impaired rhythmicity, revealing involvement of glycine in information processing within the network. These data identify glycinergic inhibition of specific targets as a cue that contributes to the synchronization of the circadian network.